Our past creates our present: a brief overview of racism and colonialism in Western paleontology. Issue 2 (May 2022) - Monarrez, Pedro M.; Zimmt, Joshua B.; Clement, Annaka M.; Gearty, William; Jacisin, John J.; Jenkins, Kelsey M.; Kusnerik, Kristopher M.; Poust, Ashley W.; Robson, Selina V.; Sclafani, Judith A.; Stilson, Kelsey T.; Tennakoon, Shamindri D.; et al.
Abstract: As practitioners of a historical science, paleontologists and geoscientists are well versed in the idea that the ability to understand and to anticipate the future relies upon our collective knowledge of the past. Despite this understanding, the fundamental role that the history of paleontology and the geosciences plays in shaping the structure and culture of our disciplines is seldom recognized and therefore not acted upon sufficiently. Here, we present a brief review of the history of paleontology and geology in Western countries, with a particular focus on North America since the 1800s. Western paleontology and geology are intertwined with systematic practices of exclusion, oppression, and erasure that arose from their direct participation in the extraction of geological and biological resources at the expense of Black, Indigenous, and People of Color (BIPOC). Our collective failure to acknowledge this history hinders our ability to address these issues meaningfully and systemically in present-day educational, academic, and professional settings. By discussing these issues and suggesting some ways forward, we intend to promote a deeper reflection upon our collective history and a broader conversation surrounding racism, colonialism, and exclusion within our scientific communities. Ultimately, it is necessary to listen to members of the communities most impacted by these issues to create actionable steps forward while holding ourselves accountable for the past.